Crystal structures of the pyrazinamide-p-aminobenzoic acid (1/1) cocrystal and the transamidation reaction product 4-(pyrazine-2-carboxamido)-benzoic acid in the molten state - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Gonnade, Rajesh G. (Acta Crystallographica Section C-Structural Chemistry, 2015)
The synthesis of pharmaceutical cocrystals is a strategy to enhance the performance of active pharmaceutical ingredients (APIs) without affecting their therapeutic efficiency. The 1: 1 pharmaceutical cocrystal of the antituberculosis drug pyrazinamide (PZA) and the cocrystal former p-aminobenzoic acid (p-ABA), C7H7NO2- C5H5N3O, (1), was synthesized successfully and characterized by relevant solid-state characterization methods. The cocrystal crystallizes in the monoclinic space group P21/n containing one molecule of each component. Both molecules associate via intermolecular O-H center dot center dot center dot O and NH center dot center dot center dot O hydrogen bonds [O center dot center dot center dot O = 2.6102 (15)angstrom and O-H center dot center dot center dot O = 168.3 (19)degrees; N center dot center dot center dot O = 2.9259 (18) angstrom and N-H center dot center dot center dot O = 167.7 (16)degrees] to generate a dimeric acidamide synthon. Neighbouring dimers are linked centrosymmetrically through N-H center dot center dot center dot O interactions [N center dot center dot center dot O = 3.1201 (18) angstrom and N-H center dot center dot center dot O = 136.9 (14)degrees] to form a tetrameric assembly supplemented by C-H center dot center dot center dot N interactions [C center dot center dot center dot N = 3.5277 (19) angstrom and C-H center dot center dot center dot N = 147 degrees]. Linking of these tetrameric assemblies through N-H center dot center dot center dot O [N center dot center dot center dot O = 3.3026 (19) angstrom and N-H center dot center dot center dot O = 143.1 (17)degrees], NH center dot center dot center dot N [N center dot center dot center dot N = 3.221 (2) angstrom and N-H center dot center dot center dot N = 177.9 (17)degrees] and C-H center dot center dot center dot O [C center dot center dot center dot O = 3.5354 (18) angstrom and C-H center dot center dot center dot O = 152 degrees] interactions creates the twodimensional packing. Recrystallization of the cocrystals from the molten state revealed the formation of 4-(pyrazine-2-carboxamido) benzoic acid, C12H9N3O3, (2), through a transamidation reaction between PZA and p-ABA. Carboxamide (2) crystallizes in the triclinic space group P1 with one molecule in the asymmetric unit. Molecules of (2) form a centrosymmetric dimeric homosynthon through an acid-acid O-H center dot center dot center dot O hydrogen bond [O center dot center dot center dot O = 2.666 (3) angstrom and O-H center dot center dot center dot O = 178 (4) degrees]. Neighbouring assemblies are connected centrosymmetrically via a C-H center dot center dot center dot N interaction [C center dot center dot center dot N = 3.365 (3) angstrom and C-H center dot center dot center dot N = 142 degrees] engaging the pyrazine groups to generate a linear chain. Adjacent chains are connected loosely via C-H center dot center dot center dot O interactions [C center dot center dot center dot O = 3.212 (3) angstrom and CH center dot center dot center dot O = 149 degrees] to generate a two-dimensional sheet structure. Closely associated two-dimensional sheets in both compounds are stacked via aromatic pi-stacking interactions engaging the pyrazine and benzene rings to create a threedimensional multi-stack structure.
Keywords: acid-amide hetero-synthon; active pharmaceutical ingredient (API); cocrystal; crystal structure; hydrogen bonding; molten-state reaction; powder diffraction; transamidation reaction

Drug-drug molecular salt hydrate of an anticancer drug gefitinib and a loop diuretic drug furosemide: an alternative for multidrug treatment - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Patwadkar, Manjusha V.; Badiger, Manohar V.; Gonnade, Rajesh G. (Journal of Pharmaceutical Sciences, 2015)
A 1:1 monohydrate salt containing gefitinib, an orally administrated chemotherapy treatment for lung and breast cancers and furosemide, a loop diuretic drug, commonly used in the treatment of hypertension and edema, has been prepared. The molecular salt crystallized in triclinic P-1 space group. The CO bond lengths (similar to 1.26 angstrom) in the COOH group show that proton transfer has occurred from furosemide to morpholine moiety of the gefitinib suggesting cocrystal to be ionic. The morpholine moiety of the gefitinib showed significant conformational change because of its involvement in conformation dictating the strong N-H center dot center dot center dot O hydrogen bonding interaction. The strong hydrogen bonding interaction between gefitinib and furosemide places their benzene rings in stacking mode to facilitate the generation of pi-stack dimers. The neighboring dimers are bridged to each other via water molecule through N-H center dot center dot center dot O, C-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O interactions. The remarkable stability of the salt hydrate could be attributed to the strong hydrogen bonding interactions in the crystal structure. Interestingly, release of water from the lattice at 140 degrees C produced new anhydrous salt that has better solubility and dissolution rate than salt hydrate. The drug-drug molecular salt may have some bearing on the treatment of patient suffering from anticancer and hypertension. (C) 2015 Wiley Periodicals, Inc. and the American Pharmacists Association
Keywords: cancer chemotherapy; cocrystals; crystal engineering; crystal structure; dissolution rate; hydrate; phase transition; solubility; stability; thermal analysis

Furosemide cocrystals with pyridines: an interesting case of color cocrystal polymorphism - Sangtani, Ekta; Sahu, Sanjay Kumar; Thorat, Shridhar H.; Gawade, Rupesh L.; Jha, Kunal K.; Munshi, Parthapratim; Gonnade, Rajesh G. (Crystal Growth & Design, 2015)
Furosemide (FS), a loop diuretic drug commonly used for the treatment of hypertension and edema, exhibited color cocrystal polymorphism with coformer 4,4'-bipyridine (4BPY) in the stoichiometry 2:1, albeit both the API and the cocrystal former are colorless. Crystallization from ethanol, isopropanol, ethanol-water (v/v, 1/1) mixture, and acetonitrile yielded pale yellow (form II, thin needles) and orange (form 1II, blocks) cocrystals concomitantly. Needles appeared from solution within a day, while the blocks were obtained after 1-2 days from the same flask, indicating that yellow needles were formed faster and the orange blocks were perhaps formed under thermodynamic conditions. Form 1I cocrystals could also be produced from the variety of common solvents. Cocrystallization of FS with 2,2'-bipyridine (2BPY) and 4-aminopyridine (4AP) gave colorless cocrystals 2 and 3, respectively, and did not exhibit polymorphism. The single-crystal X-ray structures, powder X-ray diffraction, photophysical characterization, differential scanning calorimetry, hot stage microscopy studies, and density functional theory (DFT) calculations provide insight into the structure property relationship. The common structural features observed in all of the structures is the formation of sandwich motifs comprising FS and pyridines through pi-stacking interactions. These motifs are linked differently through hydrogen bonding interactions in all three directions. The significant color difference between the two cocrystals dimorphs could be attributed to the different pi-stacking patterns and hydrogen bonding interactions between molecules of FS and 4BPY in their cocrystal structures. Investigation on the origin of the color difference using DFT calculations revealed the decrease in HOMO-LUMO gap for form 1II cocrystals (orange) compared to form 1I crystals (light yellow). The crystal-to-crystal thermal transformation of form 1I crystals to form 1II crystals of 1 suggests the role of pi-stacking assemblies in driving the self-assembly.